War on the couch: the emotionology of the new international security paradigm - Pupavac, Vanessa (Sage, 2004)
The emotional state of war-affected populations has become a central concern for international policy-makers over the last decade. Growing interest in war trauma is influenced by contemporary Anglo-American emotionology, or emotional norms, which tends to pathologize ordinary responses to distress, including anger related to survival strategies. The article critically analyzes the ascendancy of a therapeutic security paradigm in international politics, which seeks to explain the prevailing political, economic and social conditions in terms of cycles of emotional dysfunctionalism. The articles contends that international therapeutic governance pathologizes war-affected populations as emotionally dysfunctional and problematizes their right to self-government, leading to extensive external intervention. However, international therapeutic governance may be detrimental to post-war recovery as well legitimizing a denial of self-government.